(untitled) (Experimental biology, 2015)
Communities of zooplankton and macrozoobentyhos as well as ichthyofauna in the Big Almaty Lake have been studied. Results show that quantitative characteristics of zooplankton and zoobenthos are typical for those of a mountainous oligotrophic lake in autumn. In the lake has been found the only fish specie – naked osman (Gymnodiptychus dybowskii), which, most likely, was introduced to here from neighboring water basins by amateur fishers. The catch structure allows an assumption that founders were few in numbers. Biological characteristics of naked osman in the Big Almaty Lake are similar to those in other Kazakhstani water basins.